THE CHOICE OF SURGICAL TACTICS FOR THE CORRECTION OF A HIATAL HERNIA IN PATIENTS WITH CHOLELITHIASIS COMBINED WITH GASTROESOPHAGEAL REFLUX - Sh.T. Urokov; F.Y. Kholikov; L.R. Kenzhayev; Kh.N. Khamroyev (Interdisciplinary Approaches to Medicine, 2022)
Reported here are the results of the examination and surgical treatment of 70 patients with cholelithi-asis combined with hiatal hernia, of which 36 patients being in the main group and 34 patients in the comparison group who were hospitalized and underwent surgery in the clinic between 2020 and 2022. Based on an in-depth comparative analysis of early and long-term results of surgical treatment it has been proven to improve the efficiency of surgical treatment of patients with cholelithiasis, combined with gas-troesophageal reflux disease and hiatal hernia. According to different authors, hiatal hernia is combined with cholelithiasis in 8-12% of cases. Insufficient preoperative examination of this group of patients often leads to underdiagnosis of concomitant pathology requiring surgical correction, and to failure to perform the necessary surgical treatment in such cases. Many authors indicate that up to 11% of patients with cholelithiasis after cholecystectomy during re-examination have a clinic of gastroesophageal reflux disease refractory to conservative therapy and requiring surgical treatment. In practice, the tactics are chosen in a calculation method using the original formula. Thanks to the research, it was possible to optimize the tactics of surgical treatment of patients with comorbidities